Enhanced Bacterial Fitness Under Residual Fluoroquinolone Concentrations Is Associated With Increased Gene Expression in Wastewater-Derived qnr Plasmid-Harboring Strains - Kaplan, Ella; Marano, Roberto B. M.; Jurkevitch, Edouard; Cytryn, Eddie (Frontiers in Microbiology, 2018)
Plasmids harboring qnr genes confer resistance to low fluoroquinolone concentrations. These genes are of significant clinical, evolutionary and environmental importance, since they are widely distributed in a diverse array of natural and clinical environments. We previously extracted and sequenced a large ( 185 Kbp) qnrB-harboring plasmid, and several small ( 8 Kbp) qnrS-harboring plasmids, from Klebsiella pneumonia isolates from municipal wastewater biosolids, and hypothesized that these plasmids provide host bacteria a selective advantage in wastewater treatment plants that often contain residual concentrations of fluoroquinolones. The objectives of this study were therefore to determine the effect of residual fluoroquinolone concentrations on the growth kinetics of qnr plasmid-harboring bacteria; and on the copy number of qnr plasmids and expression of qnr genes. Electrotransformants harboring either one of the two types of plasmids could grow at ciprofloxacin concentrations exceeding 0.5 µg ml-1, but growth was significantly inhibited at concentrations higher than 0.1 µg ml-1. In contrast, plasmid-free strains failed to grow even at 0.05 µg ml-1. No differences were observed in plasmid copy number under the tested ciprofloxacin concentrations, but qnr expression increased incrementally from 0 to 0.4 µg ml-1, suggesting that the transcription of this gene is regulated by antibiotic concentration. This study reveals that wastewater-derived qnr plasmids confer a selective advantage in the presence of residual fluoroquinolone concentrations and provides a mechanistic explanation for this phenomenon.